Routine Postoperative Management of Blepharoplasty: A Review of Current Evidence-Based Practice - Malik, Mohsan; Shamil, Eamon; D'Souza, Alwyn Ray (Facial Plastic Surgery, 2021)
Advances in blepharoplasty have resulted in an improved understanding of preoperative risk factors, intraoperative hemostasis, and wound closure. This has reduced the risk of severe adverse events. The aim of this review is to determine the current evidence base for routine postblepharoplasty management. A literature review was performed using MEDLINE, PUBMED, and EMBASE databases. Expanded search criterion “bleph*” was combined with individual terms assessing postoperative management. Articles were assessed and qualified as per Oxford Centre of Evidence-Based Medicine levels 1 to 5 (1 = highest level of evidence). A total of 47 unique articles matched our search strategy. Most articles were a description of individual expert opinion, surveys of practice, or case series (level 4–5 evidence). Few randomized controlled trials were performed (level 2). Many articles describe the clinical experience of senior facial plastic surgeons. Our review found some evidence for postoperative cooling and preincision antisepsis to be effective. This review highlights the need for higher-quality studies to improve the evidence base for routine postoperative management.
Keywords: blepharoplasty; evidence-based review; postoperative care